Filaggrin loss-of-function mutations and association with allergic diseases. (April 2008) - Rodrííguez, Elke; Illig, Thomas; Weidinger, Stephan
Human skin constitutes a highly organized barrier against environmental agents. Its unrestricted function depends on a complex interplay between multiple proteins and lipids expressed in the terminally differentiating epithelium. Recently, attention has been drawn to the protein filaggrin, an integral part of the epidermis that plays a key role in engineering and maintaining the barrier function. Common loss-of-function mutations within the filaggrin gene have been demonstrated to cause ichthyosis vulgaris, one of the most common heritable disorders of cornification, and to represent major risk factors for atopic eczema and secondary allergic diseases. The observations on filaggrin provide striking new insights into the etiology of atopic diseases and might pave the way for the development of new therapeutic approaches.